How social capital become energy strengthening social cohesion in a plural society? - Nilma Zola; Firman Firman; Riska Ahmad (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Differentiation and diversity are highly valued in a plural society. Despite this, a plural society need a binder to reinforce interpersonal relationships, often known as social cohesiveness. Social cohesion is a social process aimed at eliminating disparities, socioeconomic inequalities, and societal rifts in order to consolidate plurality of citizenships. To survive, social cohesion requires reinforcing energy, one of which comes from social capital. This paper will explain how social capital is a source of energy that helps to strengthen social cohesion in multiple societies.